Graphene Synthesis, Properties and Applications - Maryem Badra,; Sumaya Astay, (AlQalam Journal of Medical and Applied Sciences, 2023)
Scientists and engineers have been very interested in graphene since 2004. Due to its exceptional properties, such as its large specific surface area, physicochemical properties, mechanical strength, and exceptional thermal and electronic conductivity, graphene, a two-dimensional monolayer planar sheet of sp2-bonded carbon atom, has seen a revolution in applications in recent years. To produce large amounts of high-quality graphene, various methods are employed. The synthesis of graphene using chemical, mechanical, and chemical vapor deposition processes is summed up in this study. Furthermore, the techniques for characterizing graphene and its applications in several fields of study have been covered. This article concludes by providing a brief overview and highlighting the issues of graphen and some of the recommendations that would push towards conducting scientific studies in the field of nanomaterials in more depth.